2013
DOI: 10.1097/ypg.0b013e32835d6fad
|View full text |Cite
|
Sign up to set email alerts
|

Study of the association of serotonin transporter triallelic 5-HTTLPR and STin2 VNTR polymorphisms with lithium prophylaxis response in bipolar disorder

Abstract: The 5-hydroxy tryptamine transporter (5-HTT) gene has been previously implicated in lithium response, but the roles of the triallelic 5-HTT linked promoter region (5-HTTLPR) and variable number tandem repeats in the second intron [serotonin transporter intron 2 (STin2)] have not been reported. We examined these polymorphisms in 122 patients with bipolar I disorder, among which 49 patients were classified as good responders, 49 as nonresponders, and 24 as partial responders to lithium prophylaxis. We observed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…However, another group found a contradictory result indicating that the short variant was associated with a non-response to lithium among bipolar disorder patients (Rybakowski et al, 2005b). While these studies showed some kind of association between 5-HTTLPR variants and lithium response albeit contradictory, two later studies failed to find any significant associations (Michelon et al, 2006; Manchia et al, 2009a; Tharoor et al, 2013). …”
Section: Neurotransmitter Systems and Lithiummentioning
confidence: 97%
“…However, another group found a contradictory result indicating that the short variant was associated with a non-response to lithium among bipolar disorder patients (Rybakowski et al, 2005b). While these studies showed some kind of association between 5-HTTLPR variants and lithium response albeit contradictory, two later studies failed to find any significant associations (Michelon et al, 2006; Manchia et al, 2009a; Tharoor et al, 2013). …”
Section: Neurotransmitter Systems and Lithiummentioning
confidence: 97%
“…Effects of 5‐HTT polymorphisms are seen in response to treatments other than antidepressants; Tharoor et al . reported an association of STin2 polymorphism and its combined effect with 5‐HTTLPR variants with lithium response in treatment of bipolar disorder.…”
Section: The Serotonin Systemmentioning
confidence: 99%
“…Some of these studies showed no significant association with lithium response for the following gene variants: BDNF gene, G196A/ Val66Met (Masui et al, 2006;Michelon et al, 2006;Wang et al, 2014) and rs10835210, rs11030101, rs11030102, rs12273363, rs2030324, rs2049045, rs6265", rs7103411, rs962369, and rs988748 (Drago et al, 2010); SLC6A4 gene, s/s, s/l, and l/l (Serretti et al, 2004;Masoliver et al, 2006;Michelon et al, 2006;Manchia et al, 2009); and GSK3β gene, rs3755557 (-1727A/T) (Michelon et al, 2006;Numajiri et al, 2012;Iwahashi et al, 2014), rs334558 (-50T/C) (Szczepankiewicz et al, 2006;Iwahashi et al, 2014), and rs11921360-A (Mitjans et al, 2015). On the other hand, other studies did find an association of the following variants of GSK3β, BDNF, and SLC6A4 with lithium response in patients with BD: GSK3β gene, rs334558 (−50T/C) (Adli et al, 2007;Benedetti et al, 2012;Numajiri et al, 2012;Lin et al, 2013;Mitjans et al, 2015, 3), rs6438552 (McCarthy et al, 2011, rs3755557 (-1727A/T) (Iwahashi et al, 2014), rs1732170-rs1192136 (Mitjans et al, 2015); BDNF gene, Val66Met rs6265 (Rybakowski et al, 2005;Dmitrzak-Weglarz et al, 2008;Rybakowski et al, 2012;Wang et al, 2012;Wang et al, 2014) and rs988748 (Dmitrzak-Weglarz et al, 2008); and SLC6A4 gene, l/l and s/s (Serretti et al, 2001;Benedetti et al, 2012), s allele and 10 repeat allele of STin2 (STin2.10) (Tharoor et al, 2013), and ins/del 44 pz (Rybakowski et al, 2012).…”
Section: Candidate-gene Association Studiesmentioning
confidence: 99%